2021
DOI: 10.3390/risks9050099
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fintech on Bank Risk-Taking: Evidence from China

Abstract: This article focuses on the relationship between Fintech and bank risk-taking behavior. Since Robo-Advisor is one of the mature applications of Fintech, we found that the development of Fintech will have a greater impact on small and medium-sized banks through the establishment of a Robo-Advisor model. This paper uses a benchmark regression model to analyze the municipal digital financial inclusion index compiled by Peking University and the annual report data of 155 small and medium-sized banks from 2011 to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…Nevertheless, the risk component of innovation, the essence, and prospects of risk management are not defined and are poorly studied. Selected issues related to the risks of innovation are discussed in the works of (Deng et al 2021;Kliber et al 2021;Manuylenko et al 2021;Xie 2021).…”
Section: Innovative Activities Management In Entrepreneurship In the Interests Of Sustainable Developmentmentioning
confidence: 99%
“…Nevertheless, the risk component of innovation, the essence, and prospects of risk management are not defined and are poorly studied. Selected issues related to the risks of innovation are discussed in the works of (Deng et al 2021;Kliber et al 2021;Manuylenko et al 2021;Xie 2021).…”
Section: Innovative Activities Management In Entrepreneurship In the Interests Of Sustainable Developmentmentioning
confidence: 99%
“…The aim of the study is to explore the impact of emerging fintech on bank risk-taking behavior and how the banks operating efficiency is affected by the fintech industry. There is limited literature available on how bank risk-taking behavior is affected by adopting fintech products [5,6], and recent literature mainly focuses on the impact of fintech on efficiency [7]. However, this study identifies the gap and explores the mediating effect of a bank's operating efficiency and explores whether the bank's risk-taking behavior increases or decreases by adopting fintech products and services and how it affects bank efficiency in emerging countries.…”
Section: Introductionmentioning
confidence: 98%
“…To remain competitive, banks, along with traditional banking, adopt fintech products to provide more efficient services to their customers to satisfy their needs. There is diverse opinion in the literature on the impact of fintech products used for the reduction of bank's risk-taking behavior by enhancing bank's operating efficiency [3][4][5]. Wang, Liu, and Luo [6] concluded that fintech plays a significant role to alter a bank's risk-taking behavior to achieve the bank's corporate objectives and maintain customers by providing quality services on time and reducing costs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They only promote financial inclusion and financial stability when they serve public interest. Fredman and Phillips (2022), Buckley et al (2019), FSB (2022a), Deng et al (2021) and Petrou (2018) reject the idea that digital financial innovation naturally improves financial inclusion and financial stability. They reject the idea because they believe that it underestimates the hidden risks inherent in digital financial innovation that can hinder financial stability and financial inclusion.…”
Section: Introductionmentioning
confidence: 99%